Mandatory versus discretionary spending: The status quo effect - T. Renee Bowen; Ying Chen; Hülya Eraslan (The Johns Hopkins University, Department of Economics, 2012)
Do mandatory spending programs such as Medicare improve efficiency? We analyze a model with two parties allocating a fixed budget to a public good and private transfers each period over an infinite horizon. We compare two institutions that differ in whether public good spending is discretionary or mandatory. We model mandatory spending as an endogenous status quo since it is enacted by law and remains in effect until changed. Mandatory programs result in higher public good spending; furthermore, they ex ante Pareto dominate discretionary programs when parties are patient, persistence of power is low, and polarization is low.
Keywords: C73; D61; D78; 330; budget negotiations; mandatory programs; dynamic bargaining; endogenous status quo; public goods; Gesundheitsversorgung; Öffentliche Güter; Allokationseffizienz; Verhandlungstheorie